Determinants of economic well-being and human development in Somalia: a dual analysis of GDP per capita and life expectancy - Abdikadir Ahmed Mohamed; Saido Nur Mohamed; Ikran Mohamed Weyrah; Maryan Daud Isse; Ismahan Abdi Husein (Cogent Economics & Finance)
Economic well-being and human development are essential indicators of a nation’s progress, particularly in fragile states like Somalia, where political instability, weak institutions, and external dependencies pose persistent challenges. This study examines the long- and short-run effects of institutional quality, political stability, inflation, foreign aid, foreign direct investment (FDI), and urbanization on Somalia’s GDP per capita and life expectancy from 1989 to 2022, employing the Autoregressive Distributed Lag (ARDL) model, Fully Modified Ordinary Least Squares (FMOLS), and Dynamic Ordinary Least Squares (DOLS). The findings indicate that institutional quality and FDI significantly enhance both GDP per capita and life expectancy in the long run, highlighting the importance of strong governance and foreign investment in driving economic and social progress. Conversely, foreign aid negatively affects both indicators, reinforcing concerns about aid dependency and weakened domestic productivity and healthcare systems. Political stability, inflation, and urbanization exhibit limited long-run effects, though urbanization negatively impacts both outcomes in the short run due to infrastructure constraints and healthcare pressures. These results emphasize the need for institutional reforms, investment-friendly policies, and reduced aid dependency. The study recommends policies that enhance governance, attract targeted FDI, improve urban planning, and strengthen long-term economic and social resilience in Somalia.